Photodynamic inactivation of clinical isolates of Candida using Photodithazine - Dovigo, Lívia Nordi [UNESP]; Carmello, J. C.; Carvalho, M. T.; Mima, E. G.; Vergani, Carlos Eduardo [UNESP]; Bagnato, V. S.; Pavarina, Ana Claudia [UNESP] (Taylor & Francis, 2013)
This study evaluated the photodynamic inactivation (PDI) mediated by Photodithazine® (PDZ) against 15 clinical isolates of Candida albicans, Candida glabrata and Candida tropicalis. Each isolate, in planktonic and biofilm form, was exposed to PDI by assessing a range of PDZ concentrations and light emitting diode fluences. Cell survival of the planktonic suspensions was determined by colony forming units (CFU ml-1). The antifungal effects of PDI against biofilms were evaluated by CFU ml-1 and metabolic assay. Data were analyzed by non-parametric tests (α = 0.05). Regardless of the species, PDI promoted a significant viability reduction of planktonic yeasts. The highest reduction in cell viability of the biofilms was equivalent to 0.9 log10 (CFU ml-1) for C. albicans, while 1.4 and 1.5 log10 reductions were obtained for C. tropicalis and C. glabrata, respectively. PDI reduced the metabolic activity of biofilms by 62.1, 76.0, and 76.9% for C. albicans, C. tropicalis, and C. glabrata, respectively. PDZ-mediated PDI promoted significant reduction in the viability of Candida isolates. © 2013 Taylor & Francis.
Keywords: biofilms; Candida spp.; photodynamic therapy